Contemporary Arab women's life writing and the politics of resistance - Cheurfa, Hiyem (Edinburgh University Press, 2023)
Explores the relationship between revolutionary movements and experimental life writing forms by contemporary Arab women.
Keywords: Arabic literature -- Women authors -- History and criticism.; Women -- Political activity -- Arab countries.; Arabic literature -- Women authors; Women -- Political activity; Arab countries; LITERARY CRITICISM / Middle Eastern.; Electronic books.; Criticism, interpretation, etc.